Sol-gel synthesis of nano Li1.2Mn0·54Ni0·13Co0·13O2 cathode materials using DL-lactic acid as chelating agent. Issue 5 (1st March 2021) - Chen, Can; Wu, Hongming; Zhou, Dengfeng; Xu, Dinghong; Zhou, Ying; Guo, Jianbing
Abstract: Lithium-rich cathode materials Li1·2 Mn0·54 Ni0·13 Co0·13 O2 (LMNCO) are prepared by sol-gel method using dl -lactic acid as chelating agent. The effect of pH on crystal structures, morphologies, particle sizes, and electrochemical properties of cathode materials are studied by X-ray diffractometry (XRD), scanning electron microscopy (SEM), nanoparticle analysis, charge–discharge tests, and electrochemical analysis. The Li1·2 Mn0·54 Ni0·13 Co0·13 O2 cathodes exhibit well-ordered layered structures consisting of hexagonal LiMO2 and monoclinic Li2 MnO3 with smooth surfaces and well-crystallized particles (100–500 nm). LMNCO-7.0 exhibits smaller particle sizes than LMNCO-5.5 and LMNCO-8.5 and better electrochemical performance. The first discharge capacity and Coulombic efficiency of LMNCO-7.0 are 232.31 mAh g −1 and 73.2%, respectively. After 50 cycles, discharge capacity of LMNCO-7.0 decrease to 194.93 mAh g −1 . LMNCO-7.0 cathode shows superior discharge capacity and rate performance due to its low charge transfer impedance and small average quasi-spherical particle diameter. Graphical abstract: Image 1